2010
DOI: 10.2174/1874213001003010059
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Foraging Behaviours and Growth Rates in Juveniles Contribute to the Development of Extreme Sexual Size Dimorphism in a Spider~!2010-03-14~!2010-05-31~!2010-08-13~!

Abstract: Extreme sexual size dimorphism (SSD) in temperate species is expected to be proximally caused, at least partially, by sex-specific growth rates due to the limited time available for growth and reproduction. Hence sex-specific foraging strategies are predicted to mediate differential growth rates. However, little is known about how sex differences in foraging behaviour and growth trajectories relate to the expression of pronounced SSD. Here we tested for sex-specific foraging strategies and growth rates in juve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…There, female size declined with increased elevation whereas male size did not change; this pattern, however, did not hold true for all species. Inkpen and Foellmer () argued that sex‐specific foraging behaviors and growth rates resulted in the extreme female‐biased SSD in the black and yellow garden spider, Argiope aurantia . The authors demonstrated different foraging behaviors and hence prey availabilities for females, building larger webs, and for males, constructing more conspicuous web decorations, so called stabilimenta.…”
Section: Discussionmentioning
confidence: 99%
“…There, female size declined with increased elevation whereas male size did not change; this pattern, however, did not hold true for all species. Inkpen and Foellmer () argued that sex‐specific foraging behaviors and growth rates resulted in the extreme female‐biased SSD in the black and yellow garden spider, Argiope aurantia . The authors demonstrated different foraging behaviors and hence prey availabilities for females, building larger webs, and for males, constructing more conspicuous web decorations, so called stabilimenta.…”
Section: Discussionmentioning
confidence: 99%
“…Gendered foraging strategies and differential growth rates are two additional natural selection drivers of size evolution. Whether they are proximate causes for SSD (61) or consequences of SSD is unclear. Females have higher nutritional requirements than males, which should lead to different foraging (web) biologies and developmental trajectories.…”
Section: Natural Selectionmentioning
confidence: 99%
“…It is well-known-almost a truism-that differences between sexes are common in nature and determine primary and secondary sex characters (Barrett and Hough 2013). Sexual dimorphism (SD) is observed in many organisms, such as humans, cervids (Geist and Bayer 2009), birds (Owens and Hartley 1998), spiders (Foellmer and Moya-Laraño 2007;Inkpen and Foellmer 2010) and other animals, while SD in plants is much less widely appreciated (Geber et al 1999). Meanwhile, focusing attention on the sex of plant specimens and the effects of the differences between the sexes may have significant ecological and practical significance.…”
Section: Introductionmentioning
confidence: 99%